Chemical principles - Masterton, William L.; Slowinski, Emil J. (Philadelphia : W.B. Saunders, 1977)
The chemicals provide the building blocks for everything in our physical world. Uncontrolled, their misuse can result in tragedy. As a safeguard against potential dangers, treatment processes are being implemented to mitigate or eliminate the harmful effects of chemicals. These methods are based on principles that have been developed to explain the intricate nature of the atom.
Includes index
Keywords: Chemistry